Advanced passivity-based, aging-tolerant control for a fuel cell/super-capacitor hybrid system. (December 2020) - Kong, S.; Bressel, M.; Hilairet, M.; Roche, R.
Abstract: This paper proposes an advanced aging-tolerant control for a fuel cell/super-capacitor hybrid system applied to a commercial vehicle. The controller is designed with the Interconnection and Damping Assignment-Passivity-Based Control (IDA-PBC) method to solve the converters coordination problem, where the state-of-charge of the super-capacitors and all current limitations are considered into the non-linear controller. The aging of the fuel cell is estimated in real-time by an extended Kalman filter and is integrated in the controller in order to preserve the stability of the whole system. Finally, a hardware-in-the-loop platform based on an INTEL/ALTERA FPGA is designed in order to validate the real-time operation of the algorithms for a specific case study with a fuel cell vehicle.